Detecting and Dating Chinese Housing Bubbles: Empirical Evidence form the First Tier Cities - Wu, Hanxi (Université d'Ottawa | University of Ottawa, 2014)
This paper applies a newly developed bubble detecting method, the Sup ADF test (Phillips et al., 2011), to examine the presence of housing bubbles in the first tier cities of China, namely Beijing, Shanghai, Guangzhou and Shenzhen. The empirical results confirm that there have been housing bubbles in Beijing and Shanghai and moreover, two distinct bubbles are detected in the Beijing housing market. In contrast, there is only one long, substantial bubble in Shanghai. However, there is no evidence to support the existence of housing bubbles in Guangzhou and Shenzhen.